Facile melt processing technique for the preparation of super ductile PLA–PEG multiblock copolymers: The roles of catalyst and antioxidant loadings - Wasin Koosomsuan (2019)
© 2018 Elsevier Ltd The unprecedented use of chain-scission reaction to constitute a facile and one-pot approach for the preparation of multiblock copolymers consisting of poly(lactic acid) (PLA) and poly(ethylene glycol) (PEG) from high molecular weight PLA was demonstrated. This involves two consecutive steps including melt transesterification (1) of PLA with PEG catalyzed by nontoxic titanium-based catalyst in an internal mixer to form short-chain block copolymers, followed by chain extension (2) using hexamethylene diisocyanate (HDI) to obtain long-chain multiblock copolymer products. Due to the primary concern on the counterbalance between chain-scission and exchange reactions, the effects of catalyst and antioxidant loadings were investigated. Excessive addition of the catalyst beyond optimal point not only deteriorated the formation of desirable products in step 1 (due to accelerated thermal degradation of PEG), but also posed detrimental effects on the efficacy of the chain extension in step 2 and mechanical properties of the final products. When appropriate amount of catalyst (0.75 phr) was used in combination with antioxidant, the long-chain copolymers exhibited extraordinarily high ductility with strain-to-break values exceeding 500%.